Breaking the boundary between personal- and work-life skills: parenting as a valuable experience for knowledge workers. (10th April 2009) - Rimbau-Gilabert, Eva; Miyar-Cruz, David; Lopez-de Pedro, Jose Maria
The idea that the skills that are useful in companies are in opposition to the skills needed in family life has created a separation between work and personal areas, which diminishes the value placed on the learning obtained in the family environment. In opposition to this view, this paper argues that the informal learning obtained through child rearing can provide tacit knowledge that may be valuable in work situations. We review the literature from the field of developmental psychology, which has focused on parenting as a context for personal development, and suggest that two tacit skills derived from parenting are especially valuable in work settings, namely, flexible thinking and allocentric thinking. The organisational value of these skills is analysed with an emphasis on its usefulness for knowledge workers and the general implications are discussed.